Development of a theory and evidence-based program to promote community treatment of fevers in children under five in a rural district in Southern Ghana: An intervention mapping approach - Mercy Abbey; L. Kay Bartholomew; Margaret A. Chinbuah; Margaret Gyapong; John O. Gyapong; Bart van den Borne (BMC, 2017)
Abstract Background This paper describes the development and implementation of a program to promote prompt and appropriate care seeking for fever in children under the age of five. Designed as a multicomponent program, the intervention comprises elements to influence the behavior of caregivers of children, Community Health Workers, professional health care providers and the wider community. Methods Following the six fundamental steps of the Intervention Mapping protocol, we involved relevant stakeholders from the commencement of planning to program end. The IM protocol also recommends various behavior change methods to guide intervention development. Results The intervention components implemented were successful in achieving program goals. For example, the intervention resulted in the primary outcome of reductions in all-cause mortality of 30% and 44%, among children treated with an antimalarial and those treated with the antimalarial plus an antibiotic respectively. Most Community Health Workers were retained on the program, with an attrition rate of 21.2% over a period of 30 months and the Community Health Workers rate of adherence to performance guidelines was high at 94.6%. Conclusion We were able to systematically develop a theory- and evidence-based health promotion program based on the Intervention Mapping protocol. This article contributes to the response to recent calls for a more detailed description of the development of interventions and trials. The intervention mapping approach can serve as a guide for others interested in developing community- based health interventions in similar settings.